HUBUNGAN KEPATUHAN MENGGOSOK GIGI DENGAN TINGKAT KEJADIAN KAREIS PADA SISWA KELAS IV DAN V DI SDS PELANGI MEDAN - Mitra Sejajar Telaumbanua; Hizkianta Sembiring (PT. Hasba Edukasi Mandiri, 2025)
Dental caries is tissue damage on the surface of the teeth. This tissue damage is usualy characterized by the disappearance of the hard tissue structure on the teeth due to acid deposits made by plaque bacteria that accumulate high on the surface of the teeth. Dental caries is a problem that often occurs among the community,especially in elementary school age children. Dental caries can be caused by negligence in maintaining oral and dental caries. To determine the relationship of teeth brushing compliance with rate of caries incident in class IV and V student at SDS Pelangi. This study uses quantitative research methods with a cross sectional approach. The sampling technique researchers in determining respondents is the total sampling technique. The data analysis technique used is the chi square test. This study showed a relationship of tooth brushing compliance with rate of caries incident in class IV dan V students at SDS Pelangi Medan with a p value = <,001 or p < 0,005. Based on the research conducted, there is significant relathionship of tooth brushing compliance with rate of caries incident in class IV dan V students at SDS Pelangi Medan. With this research, it is hoped that future researchers will develop this research using different methods such as experiments or qualitative ones.